Marie Antoinette : Princess of Versailles, Austria-France, 1769 - Lasky, Kathryn (New York, NY : Scholastic Inc., 2013)
In 1769, thirteen-year-old Maria Antonia Josepha Johanna, daughter of Empress Maria Theresa, begins a journal chronicling her life at the Austrian court and her preparations for her future role as queen of France.
Booklist
Books for the Teen Age (NYPL)
School Library Journal
Booklist, April 2000
Books for the Teen Age (NYPL), January 2002
Bulletin (Center for Children's books), June 2000
Keywords: Marie Antoinette, -- Queen, consort of Louis XVI, King of France, -- 1755-1793 -- Childhood and youth -- Juvenile fiction; Marie Antoinette, -- Queen, consort of Louis XVI, King of France, -- 1755-1793 -- Childhood and youth -- Fiction; Marie Antoinette, -- Queen, consort of Louis XVI, King of France, -- 1755-1793 -- Fiction; Diaries -- Fiction; Kings, queens, rulers, etc. -- Fiction; Diaries -- Fiction; Kings and rulers -- Fiction; Diary fiction